2011
DOI: 10.1074/jbc.m111.255026
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Light and Heavy Chain Linkage of Human Immunoglobulin G1 (IgG1) by Radical Reactions

Abstract: We report that the production of hydrogen peroxide by radical chain reductions of molecular oxygen into water in buffers leads to hinge degradation of a human IgG1 under thermal incubation conditions. The production of the hydrogen peroxide can be accelerated by superoxide dismutase or redox active metal ions or inhibited by free radical scavengers. The hydrogen peroxide production rate correlates well with the hinge cleavage. In addition to radical reaction mechanisms described previously, new degradation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 51 publications
1
34
0
Order By: Relevance
“…In general, hinge modifications are induced by exposure to heat [, ], H 2 O 2 , acidic/basic pH , or UV light . Disulfide bonds are strongly involved in these processes that also comprise different cleavage processes , thioether bond formation and Cys racemization . Also iso‐Asp formation is an often observed variant of these modification processes .…”
Section: Disulfide‐ and Hinge‐related Modificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, hinge modifications are induced by exposure to heat [, ], H 2 O 2 , acidic/basic pH , or UV light . Disulfide bonds are strongly involved in these processes that also comprise different cleavage processes , thioether bond formation and Cys racemization . Also iso‐Asp formation is an often observed variant of these modification processes .…”
Section: Disulfide‐ and Hinge‐related Modificationsmentioning
confidence: 99%
“…These investigations elucidated the underlying reaction mechanisms that lead to diverse hinge modification and fragmentation (see also Fig. ): Disulfide ‐linked Fab fragments were described as a result of radical transfer between the LC‐HC disulfide bond and the first HC‐HC disulfide bond including the upper hinge His as radical center. This resulted in cleavage of any one peptide bond between these two disulfide bonds (formation of ragged termini or ladder formation as denoted above).…”
Section: Disulfide‐ and Hinge‐related Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyl radicals generated in the presence of Cu 2C sulfate have been implicated in the cleavage of the IgG1 hinge region. 12 Our data using mannitol showed that there was no impact on fragmentation in the presence of this hydroxyl radical scavenger. Nonetheless, it has been shown that a hydroxyl radical generated in close proximity to the site of oxidation may be consumed before it can diffuse, which would render mannitol unable to quench the reaction.…”
Section: Discussionmentioning
confidence: 88%
“…11 Non-enzymatic fragmentation, on the other hand, can be observed by direct hydrolysis, 6 b-elimination, 7 and free-radical catalysis of peptide bond cleavage in mAbs, 12 and metal-mediated oxidative cleavage in peptides. 13 Fragmentation kinetics by non-enzymatic methods has been shown to vary with pH; pH 6 has the lowest rate of cleavage and rates increase in both more acidic and basic conditions, 14 and storage temperature.…”
Section: Introductionmentioning
confidence: 99%